Writing Strategies Used by Indonesian EFL Graduate Students - Nanik Rahmawati (IJER (Indonesian Journal of Educational Research), 2019)
The study is aimed at investigating the English language writing strategies used by Indonesian graduate students at an academic writing class. The objectives of this study were to determine the types of writing strategies used by the students and to find out why the students employed such strategies. The study applied a qualitative method approach. A structured interviews and open-ended questionnaire based on Cazrl and Petric writing strategies inventory were employed in collecting data. The result showed that students used three major strategies which are before, during and after writing strategies. Secondly, the reason why they employed such strategies are students’ belief, students’ awareness, students’ language proficiency, writing time, and writing activity environment. The implication of the study are that writing time and environment may become a foundation to develop a teaching method or technique which may be implemented in a classroom teaching activity to achieve a better writing outcome. Moreover, By understanding the differences of the writing strategies employment, it exploits what differ the high and the low to upgrade the students writing quality into a better writing.